Efektivitas Program Pelayanan Jaminan Kesehatan Daerah (JAMKESDA) Di Rumah Sakit Umum Kota Bitung - Pipa, Felix; Lengkong, Daicy; Rorong, Arie (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Hospital is a health care institution that organizes personal health services in plenary thatprovides inpatient, outpatient, and emergency department. In connection with the Hospital opened healthservices through programs that one Regional Health Insurance program (JAMKESDA) which is aprogram for the poor that health care costs are guaranteed by the Government.This study is intended to answer the "Is service health insurance program area (JAMKESDA) in the cityof Bitung is already effective. This study uses a qualitative method. Data source / informant study is thehead of the general hospital one person, public hospital employees 10 people, and participants Jamkesda20 people, so the total number of informants there were 31 people. Primary data collection using thequestionnaire technique and help with the interview.Results of the data analysis showed that the implementation of the regional health insurance servicesprogram (JAMKESDA) in the city of Bitung is already operating effectively, although not optimal. Basedon the results of these studies conclude that it is not optimal effectiveness of the implementation of theRegional Health Insurance services program (JAMKESDA) related to the implementation of satisfactionindicators and indicators of adaptation that has not been effective, both the level of satisfaction ofemployees / employee hospitals and patients and families of patients who have not been satisfied on theservice they received.Referring to some of the findings in this study, then to optimize the achievement of effectiveimplementation of the Regional Health Insurance program (JAMKESDA) in city Bitung forward, needs tobe optimized implementation of satisfaction indicators and indicators of adaptation, through increasing itscapacity to adjust to the dynamics and demands of internal environment and externally.Key words: : Effectiveness of Care Regional Health Insurance Program (JAMKESDA).